The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2147/ijn.s28185
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of Tet1 peptide functionalized polymersomes to the rat cochlear nerve

Abstract: Polymersomes are nanosized vesicles formed from amphiphilic block copolymers, and have been identified as potential drug delivery vehicles to the inner ear. The aim of this study was to provide targeting to specific cells within the inner ear by functionalizing the polymersome surface with Tet1 peptide sequence. Tet1 peptide specifically binds to the trisialoganglioside clostridial toxin receptor on neurons and was expected to target the polymersomes toward the cochlear nerve. The Tet1 functionalized PEG-b-PCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…The accumulation of hyaluronic acid might contribute to an increased permeability and microcirculation inflammation in renal ischemic reperfusion injury [20]. Previous studies demonstrated that the rodent inner ear was an excellent organ for the evaluation of nanoparticle biocompatibility due to its sophisticated barrier system [21][22][23], and AgNPs were capable of disrupting the blood-inner ear barriers, as indicated by magnetic resonance imaging (our unpublished data). Therefore, the current research was designed to verify the hypothesis that an accumulation of glycosaminoglycan associated with the up-regulation of hyaluronic acid in the basement membrane is involved in the kidney and cochlea impairments following exposure to AgNPs.…”
Section: Introductionmentioning
confidence: 88%
“…The accumulation of hyaluronic acid might contribute to an increased permeability and microcirculation inflammation in renal ischemic reperfusion injury [20]. Previous studies demonstrated that the rodent inner ear was an excellent organ for the evaluation of nanoparticle biocompatibility due to its sophisticated barrier system [21][22][23], and AgNPs were capable of disrupting the blood-inner ear barriers, as indicated by magnetic resonance imaging (our unpublished data). Therefore, the current research was designed to verify the hypothesis that an accumulation of glycosaminoglycan associated with the up-regulation of hyaluronic acid in the basement membrane is involved in the kidney and cochlea impairments following exposure to AgNPs.…”
Section: Introductionmentioning
confidence: 88%
“…Peptides are smaller and less immunogenic than antibodies, and attaching several peptides on the surface of a single polymersome is possible. Like antibodies, some peptides (e.g., Tet-1 [31] and PR_b [32]) can be used to target a specific cell’s surface receptors or molecules. Moreover, some peptides, such as the transactivator of transcription (TAT, derived from the human immunodeficiency virus), and many other chimeric peptides, such as transportan [42], are known as cell-penetrating peptides.…”
Section: Biomedically Translatable Polymersomesmentioning
confidence: 99%
“…[1][2][3][4][5] So far, several liposomal anticancer drugs have been approved by the US Food and Drug Administration (FDA) and become commercially available on the market. Typical examples include liposomal paclitaxel (PTX; Lipusu ® ), 6 doxorubicin (Myocet ® ), daunorubicin (DaunoXome ® ), and cytarabine (DepoCyt ® ).…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, we hypothesized that the hybrid nanoparticles may combine the advantages of liposomes and polymeric micelles, such as safety and stability and improve cargo cellular uptake and tumor accumulation. Poly(ethylene glycol)-b-poly(ε-caprolactone) (PEG-b-PCL) diblock copolymer has been widely used to prepare PEGcoated micelles 2,4,[14][15][16][17] and is a promising PEG modification tool for stealth nanoparticles for the following reasons: 1) the synthesis of PEG-b-PCL is facile and is adaptable to mass manufacture; 18 2) PEG-b-PCL micelles can stay in the bloodstream for a prolonged time and are capable of efficient cell entry; 19,20 and 3) PEG-b-PCL is biocompatible, since PEG and PCL are both FDA-approved for use in humans. Moreover, PEG-b-PCL micelles carrying PTX (Genexol-PM) are approved in several Asian countries for cancer therapy and are in Phase III clinical trials in the US.…”
Section: Introductionmentioning
confidence: 99%